E-104 The use of mechanical thrombectomy in posterior circulation acute ischemic strokes. (22nd July 2019) - Sweid, A; Hafazalla, K; Tjoumakaris, S; Xu, V; Shivashankar, K; Alexander, T; Gooch, M; Herial, N; Chalouhi, N; Rosenwasser, R; Jabbour, P
Abstract : Objective: 20% of all acute ischemic strokes (AIS) occur in the posterior circulation (PC), which carry a high mortality rate close to 95%. Early recanalization improves outcomes as shown by several reports. Often trials excluded patients with posterior circulation strokes. We sought to investigate the prevalence, safety, and the clinical outcomes of PC-MT at our institution. Methods: A retrospective review of patients presenting with PC AIS who underwent mechanical thrombectomy at a tertiary referral center between 2010 and 2018. Results: Out of 453 patients who underwent mechanical thrombectomy for AIS, 45 patients had a PC stroke (av age 58 years, 56% male). The mean NIHSS upon admission was 17 (95%CI:14–20). The mean time from symptoms onset to groin puncture was 9 hours (95%CI:6–11), the mean procedure time was 53 minutes (95%CI:43–64) and mean time to revascularization, from symptoms onset was 866 minutes (95%CI:602–1129). Only 33% received tPA. Vessels involved included the basilar artery (87%, n=39), the posterior cerebral artery (4%, n=2), and the vertebral artery (9%, n=4). The procedures were divided into stentreiver alone (22%, n=10), aspiration alone (13%, n=6), and stentreiver with aspiration (51%, n=23), and failed procedure in 13% (n=6) of individuals. Most procedures required one pass to recanalize the vessel (44%, n=20). TICI > 2b was achieved in 69% of the subjects. Mean length of stay was 11 days (95%CI:8–14). Mortality rate was 38% and independent functional outcome of mRS < 2 at three months was seen in 20% of the patients. On univariate analysis extravasation was significantly higher in PC compared to anterior circulation (AC) (9% vs 4%, p<0.01) as well as post-procedural sICH (13% vs. 4%, p=0.01); vessel recanalization (TICI > 2b) was significantly lower in PC compared to AC (70% vs 90%, p<0.01); mortality rate was significantly higher in patients with PC compared to AC (38% vs 9%, p<0.01). On multivariate analysis AC had a significantly shorter LOS by about three days, compared to PC (coef:-3.04, 95%CI: -6.05 to -0.14, p<0.05). There was no difference in odds of achieving a good TICI score. The AC group also had almost four times greater odds of having a good mRS (OR: 3.69, 95%CI:1.06–12.8, p<0.05). They also had significantly lower odds of mortality, by around eighty-eight percent (OR:0.12, 95%CI: 0.05–0.31, p<0.01). Conclusions: MT is a safe and efficacious first-line therapy for PC strokes. PC-MT provides a high rate of recanalization without procedural complications. Improvement in functional outcome remains low, and mortality remains high, but with a much better outcome than leaving the disease untreated. Disclosures: A. Sweid: None. K. Hafazalla: None. S. Tjoumakaris: None. V. Xu: None. K. Shivashankar: None. T. Alexander: None. M. Gooch: None. N. Herial: None. N. Chalouhi: None. R. Rosenwasser: None. P. Jabbour: None.